The impact of sugar-sweetened beverage intake on rat cardiac function. Issue 3 (March 2019) - Driescher, Natasha; Joseph, Danzil E.; Human, Veronique R.; Ojuka, Edward; Cour, Martin; Hadebe, Nkanyiso; Bester, Dirk; Marnewick, Jeanine L.; Lecour, Sandrine; Lochner, Amanda; Essop, M. Faadiel
Abstract: Aims: Although there is evidence linking sugar-sweetened beverage (SSB) intake with the development of cardio-metabolic diseases, the underlying mechanisms remain unclear. The current study therefore evaluated the effects of SSB consumption by establishing a unique in-house in vivo experimental model. Main methods: Male Wistar rats were divided into two groups: a) one consuming a popular local SSB (SSB- Jive), and b) a control group (Control-water) for a period of three and six months (n = 6 per group), respectively. Rats were gavaged on a daily basis with an experimental dosage amounting to half a glass per day (in human terms) (SSB vs. water). Cardiac function was assessed at baseline (echocardiography) and following ex vivo ischemia-reperfusion of the isolated perfused working rat heart. Oral glucose tolerance tests and mitochondrial respiratory analyses were also performed. In addition, the role of non-oxidative glucose pathways (NOGPs), i.e. the polyol pathway, hexosamine biosynthetic pathway (HBP) and PKC were assessed. Key findings: These data show that SSB intake: a) resulted in increased weight gain, but did not elicit major effects in terms of insulin resistance and cardiac function after three and six months, respectively; b) triggered myocardial NOGP activation after three months with a reversion after six months; and c) resulted in some impairment in mitochondrial respiratory capacity in response to fatty acid substrate supply after six months. Significance: SSB intake did not result in cardiac dysfunction or insulin resistance. However, early changes at the molecular level may increase risk in the longer term.